KELAYAKAN BAHAN AJAR INTERAKTIF E-MODUL PEMBELAJARAN KIMIA PADA MATERI KOLOID BERBASIS KEARIFAN LOKAL PAPUA - Kelana, Ardian Hangga; Irawan, Sakka; Karubaba, Marice; Sahar, Adnan (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study aims to determine the feasibility of interactive e-module chemistry teaching materials on colloid material based on Papuan local wisdom. The research method used is Research and Development (R and D). The research sample was conducted in class XI IPA 1 SMA YPK Diaspora Kotaraja Jayapura with a total of 30 students. The results of the study indicate that: the feasibility of interactive e-module chemistry teaching materials on colloid material based on Papuan local wisdom based on material validators obtained an average of 88% with the category